Cobalt Compounds and Applications - Yıldız, Yasemin; Manzak, Aynur (IntechOpen, 2019)
In addition to theoretical information, this book provides information on cobalt compounds and nanoparticles made at selected universities and research centers around the world.This book includes information on new cobalt approaches, nanostructured cobalt, and new catalysts in some reactions and biological systems and technologies.I deeply appreciate the authors? great contributions to this work.We hope that the book will shed light on new horizons for scientists, engineers, and students.